2014
DOI: 10.1002/2013gl058744
|View full text |Cite
|
Sign up to set email alerts
|

The stress shadow problem in physics-based aftershock forecasting: Does incorporation of secondary stress changes help?

Abstract: Main shocks are calculated to cast stress shadows across broad areas where aftershocks occur.Thus, a key problem with stress-based operational forecasts is that they can badly underestimate aftershock occurrence in the shadows. We examine the performance of two physics-based earthquake forecast models (Coulomb rate/state (CRS)) based on Coulomb stress changes and a rate-and-state friction law for their predictive power on the 1989 M w = 6.9 Loma Prieta aftershock sequence. The CRS-1 model considers the stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…The response of the −ΔCFS seismicity in Region III (Figure h) is especially enigmatic: it shows an immediate increase at the time of the Ocotillo event, inconsistent with the simple CFS predictions, although this elevated rate then drops below the pre‐Ocotillo Omori prediction some 20 days after Ocotillo, which is indicative of a delayed stress shadow effect. These results suggest that considering individual receiver focal mechanisms does not improve our ability to evaluate the relationship between static stress and seismicity, which is consistent with previous studies (Cattania et al, ; Meier et al, ; Segou & Parsons, ).…”
Section: Coulomb Stress Modelingsupporting
confidence: 90%
“…The response of the −ΔCFS seismicity in Region III (Figure h) is especially enigmatic: it shows an immediate increase at the time of the Ocotillo event, inconsistent with the simple CFS predictions, although this elevated rate then drops below the pre‐Ocotillo Omori prediction some 20 days after Ocotillo, which is indicative of a delayed stress shadow effect. These results suggest that considering individual receiver focal mechanisms does not improve our ability to evaluate the relationship between static stress and seismicity, which is consistent with previous studies (Cattania et al, ; Meier et al, ; Segou & Parsons, ).…”
Section: Coulomb Stress Modelingsupporting
confidence: 90%
“…Modeling stresses from aftershocks is particularly challenging, since slip distributions or even focal planes are not always known. In fact, Meier et al [] found that including ΔCFS from aftershocks decreases the predictive power of the Coulomb hypothesis, and Segou and Parsons [] found a negligible improvement in predictability. The difference between these results and the improvement in performance in our models may be due to the fact that for most of the events, we assumed an isotropic stress field instead of the full stress field from the focal mechanism.…”
Section: Discussion and Further Analysismentioning
confidence: 99%
“…When employing equation to evaluate seismicity rate, a common difficulty is that events may occur in the stress shadow of previous events, where Δ S may be very low, and hence, from equations and , γ may be extremely large [e.g., Segou and Parsons , ; Cattania et al , ]. Very large model γ , and hence low R , evaluated in a shadow zone will generally persist well beyond the early postseismic period.…”
Section: Application To Southern California Seismicitymentioning
confidence: 99%
“…Previous studies have shown that stress shadows are drastically reduced in rate and state when considering small‐scale (unresolved) heterogeneity in the stress field [ Marsan , ; Helmstetter and Shaw , ; Cattania et al , ]. Therefore, the presence of predicted strong stress shadows, and consequently unrealistically low predicted seismicity rates, reflects to a large extent uncertainty in the source models plus the ignorance of other physics that may promote triggering in a shadow of a main shock, e.g., secondary stress changes on nearby faults [ Segou and Parsons , ]. To circumvent this problem, we introduce smoothing of the reciprocal of the state variable, γ −1 .…”
Section: Application To Southern California Seismicitymentioning
confidence: 99%
See 1 more Smart Citation